CATEGORIES OF COMPUTER SYSTEMS ALGORITHMS - A. V. Poltavskiy; E. Y. Rusyaeva (Научный вестник МГТУ ГА)
Philosophy as a frame of reference on world around and as the first science is a fundamental basis, "roots" (R. Descartes) for all branches of the scientific knowledge accumulated and applied in all fields of activity of a human being person. The theory of algorithms as one of the fundamental sections of mathematics, is also based on researches of the gnoseology conducting cognition of a true picture of the world of the buman being. From gnoseology and ontology positions as fundamental sections of philosophy modern innovative projects are inconceivable without development of programs,and algorithms.